(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In this paper, we introduce and investigate a pair of symmetric multi-dimensional variational fractional control problems. To this end, first, we formulate an updated concept of pseudoinvexity associated with multiple integral type functionals. Further, we establish a very important connection between the objective functionals of the studied symmetric models.